2019
DOI: 10.9734/ajaees/2019/v31i230130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Financing on Nigeria Economy

Abstract: The importance of agricultural surplus for the structural transformation accompanying economic growth is often addressed by development economists. In view of this, the study empirically assesses the impact of agricultural finance on the growth of Nigerian economy. This paper employed secondary data and econometric techniques of Ordinary Least Square (OLS) of multiple regression estimates. The result of the model used suggests that the productivity of investment will be more appropriately financed with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Accordingly, 17% of the difference between long-term, equilibrium, or the desired amount of agricultural GDP and the current or observed agricultural GDP is reduced each year. Findings in the literature show that agricultural credits positively affect agricultural productivity (SHAH et al, 2008;AYAZ & HUSSAIN, 2011;SALEEM & JAN, 2011;AGUNUWA et al 2015;AWOTIDE et al 2015;CHISASA & MAKINA, 2015;NNAMOCHA & EKE, 2015;UDOKA et al 2016;OGBUABOR & NWOSU, 2017;DURAMAZ & TAS, 2018;ADEMOLA, 2019;TAMBI & BIME, 2019). IQBAL et al (2003), SIAL et al (2011, REHMAN et al (2017), KOC et al (2019); REHMAN et al (2019), found that agricultural credits have a positive and statistically significant effect on agricultural GDP.…”
Section: Ols Regression For Parameter Relationsmentioning
confidence: 99%
“…Accordingly, 17% of the difference between long-term, equilibrium, or the desired amount of agricultural GDP and the current or observed agricultural GDP is reduced each year. Findings in the literature show that agricultural credits positively affect agricultural productivity (SHAH et al, 2008;AYAZ & HUSSAIN, 2011;SALEEM & JAN, 2011;AGUNUWA et al 2015;AWOTIDE et al 2015;CHISASA & MAKINA, 2015;NNAMOCHA & EKE, 2015;UDOKA et al 2016;OGBUABOR & NWOSU, 2017;DURAMAZ & TAS, 2018;ADEMOLA, 2019;TAMBI & BIME, 2019). IQBAL et al (2003), SIAL et al (2011, REHMAN et al (2017), KOC et al (2019); REHMAN et al (2019), found that agricultural credits have a positive and statistically significant effect on agricultural GDP.…”
Section: Ols Regression For Parameter Relationsmentioning
confidence: 99%
“…The finding aligns with the study of Oyenbo and Rekwot (2014); Abula and Ben (2016);Abula and Ben (2016); Inusa, Daniel, Dayagal and Chiya (2018) noted the importance of Agriculture to economic development, especially in less developed countries (LOCs) like the Sub-Saharan African countries where industrialization is under developed. Oyenbo and Rekwot (2014) indicated that agricultural production was significant in influencing the favorable trend of economic growth, while on the other hand the findings of Ademola (2019) found that agricultural output level in Nigeria during the period review by the study for has contributed negatively to the level of economic development. Despite the fact so many funds from different sources have been expended on the sector.…”
Section: Discussion Of Findingmentioning
confidence: 99%
“…Several researchers (Abbas, Muhtaraom, Badriyah and Kadir, 2020;Abukari, Oztoronci and Veziroglu, 2016;Ademola, 2019;Brown and Iyabode, 2020;Kakar, Kiani and Baig, 2016) have recently explored the influence of climate change agriculture output using various econometric methodologies. Rashid, Husnain, Shakoor and Husnain (2020) empirically found the influence of climate fluctuations on Pakistan's cotton crop and found out that the negative effect of increasing the minimum temperature outweighs the beneficial effect of increasing the maximum temperature.…”
Section: Review Of Literaturementioning
confidence: 99%